2012
DOI: 10.1021/ja3019065
|View full text |Cite
|
Sign up to set email alerts
|

Closely Stacked Oligo(phenylene ethynylene)s: Effect of π-Stacking on the Electronic Properties of Conjugated Chromophores

Abstract: In this work, a bicyclo[4.4.1]undecane scaffold is used to hold oligo(phenylene ethynylene) units in a cofacially stacked arrangement along the entire length of the conjugated units. We study the impact that the resulting strong interchain interactions have on the photophysical properties. The length of the individual oligomer branches was varied from three to five rings to investigate the effect of conjugation on the electronic properties of the stacked segments. Absorption and fluorescence spectra were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 42 publications
3
80
0
Order By: Relevance
“…24,25 Among the different types of linkers, hairpin-shaped rigid linkers can promote the formation of intramolecular π-stacked structures. [26][27][28][29][30] We have recently reported the synthesis of polymers with layered aromatic rings using a xanthene scaffold as a hairpin-shaped linker; these polymers exhibit intramolecular π-stacked structures with multiple aromatic rings stacked along a single polymer chain. [31][32][33][34][35][36] They can be regarded as the assembly of several small π-conjugated units.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Among the different types of linkers, hairpin-shaped rigid linkers can promote the formation of intramolecular π-stacked structures. [26][27][28][29][30] We have recently reported the synthesis of polymers with layered aromatic rings using a xanthene scaffold as a hairpin-shaped linker; these polymers exhibit intramolecular π-stacked structures with multiple aromatic rings stacked along a single polymer chain. [31][32][33][34][35][36] They can be regarded as the assembly of several small π-conjugated units.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of our process indicated that the entire sequence to produce 13.6 g of 1 could be carried out in three days at a cost that is significantly less than that of the commercial material. The conversion of this diol to 6,7-dimethylphthalazine has been previously reported [13]. (1) In a 250-mL, heavy-walled, round-bottomed pressure vessel (CHEMGLASS CG-1880-R-03) equipped with a magnetic stirrer was placed 2,3-dimethyl-1,3-butadiene (2, 10.0 g, 121.7 mmol), dimethyl acetylenedicarboxylate (3, 17.3 g, 121.7 mmol) and toluene (70 mL).…”
Section: Methodsmentioning
confidence: 69%
“…Compared to the monomer 6, the lowest-energy absorption bands of the dimers 2 are bathochromically shifted, suggesting narrowing of the HOMO-LUMO gap owing to throughspace interaction. [24] Interestingly, the red-shifts in the dimers 2 c, 2 b, and 2 a becomes smaller in this order, indicating that the distortion weakens the through-space interaction between two p-systems. The similar feature is also observed for pextended derivative 5.…”
mentioning
confidence: 87%